2010
DOI: 10.1080/15433714.2010.498669
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Practitioners and Practice Evaluation: How Are We Doing?

Abstract: Practice evaluation is an important component of evidence-based social work practice. Previous research in this area has concluded that even though social workers receive evaluation training, it remains under-utilized in practice. This study discusses the results of a survey of 134 social workers across different social work settings, positions, and level of preparation, examining incidence and type of evaluation activity, training received, and barriers related to implementing practice evaluation in the pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Many staff in prevention programmes are social workers. Despite receiving evaluation training during completion of their degrees, literature suggests most social workers engage in very limited evaluation activities (e.g., client satisfaction and descriptive reporting of services provided) and cite time as a barrier to more complex evaluation efforts (Baker, Stephens, & Hitchcock, ). In response to these limitations, most prevention agencies conduct simple analyses, such as comparing mean pretest and post‐test scores and combine all families—regardless of their unique family characteristics—in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Many staff in prevention programmes are social workers. Despite receiving evaluation training during completion of their degrees, literature suggests most social workers engage in very limited evaluation activities (e.g., client satisfaction and descriptive reporting of services provided) and cite time as a barrier to more complex evaluation efforts (Baker, Stephens, & Hitchcock, ). In response to these limitations, most prevention agencies conduct simple analyses, such as comparing mean pretest and post‐test scores and combine all families—regardless of their unique family characteristics—in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Social work practitioner evaluation is an underutilised area of practice research (Baker, Stephens, & Hithcock, 2010). In their research of 134 social workers across different practice settings in North Carolina, they concluded that while the social workers who participated in their research had some practice evaluation training in their degree courses, they were not involved in evaluation work outside collecting basic statistics.…”
Section: Research-minded Practicementioning
confidence: 97%
“…More recently, a survey of social work practitioners conducted by Baker, Stephens, and Hitchcock (2010) found that although most social workers were trained in evaluation methodology as part of their educational program, very few were engaged in practice evaluation efforts beyond the collection of agency statistics. Finding more effective ways to facilitate the transfer of research knowledge and skills from the classroom to the field is an important issue for the social work profession because the demonstration of practice effectiveness is essential to both ethical service delivery and the ability to secure and retain funding.…”
Section: Literature Reviewmentioning
confidence: 98%